ASPECTS OF SCOLIOSIS RECOVERY BY ORTHOSING IN PREPUBERTY - Mihai Constantinescu (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This article refers to some general aspects regarding the approach of scoliosis recovery programmes aimed at prepubertal children aged between 10-14, by the uses of brace-type orthoses.